Ethics and education research - Brooks, Rachel 1971-; Te Riele, Kitty; Maguire, Meg 1949- (Research methods in education, 2014)
Drawn from the authors' experiences in the UK, Australia and mainland Europe and with contributions from across the globe, this clear and accessible book includes a wide range of examples. The authors show the reader how to: identify ethical issues which may arise with any research project, gain informed consent, provide information in the right way to participants, and present and disseminate findings in line with ethical guidelines.